Social Media Neologisms in Bangladesh: Linguistic Creativity or Catastrophe - Mostafa, Massrura; Jamila, Marium (Indonesian Journal of English Language Studies (IJELS), 2024)
This paper made a lexico-semantic analysis of several social media neologisms, checked their frequencies on the online corpus WebCorp, and checked their usage regarding derivations, conversions, or compounding on Bangladeshi online webpages and newspapers. The selected words were also checked in the recorded conversations and focus group interview scripts collected from the students of the two public universities in Bangladesh to scrutinize the different forms of the words found on WebCorp. The findings revealed that the words were mostly frequent in the written as well as in the spoken languages as nouns and all other formations of each of the base words were not that frequent. Some of the formations seemed to be forced creations. The discussion exposes that these neologisms have been inserted into the Bangla language without any significant changes as if they were Bangla words. Thus, they have become an inseparable part of the Bangla language and important examples of linguistic creativity. Their usage also symbolizes modern identity.